Microbial Activity of Rhizospheric Soil and Leaf Litter on Livestock Farms Sown with Bothriochloa Pertusa (L) A. Camus and Dichantium Aristatum - Cordero, Alexander Perez; Vergara, Donicer E. Montes; Mendoza, Yelitza Aguas (Journal of Posthumanism, 2024)
Soil use and management can significantly affect the labile and humified fractions of soil organic matter, to the detriment of biological activity. The aim of the present study was to evaluate the microbial activity of rhizospheric soil and rhizospheric soil plus litter on cattle farms cultivated with Bothriochloa pertusa (L) A. Camus and Dichantium aristatum pastures. Samples of soil, litter and the combination of soil + litter were collected from cattle farms in the municipality of Corozal, department of Sucre, Colombia. The respiratory activity of the soil was determined using the incubation method. The results of the present study indicate that the treatments with the lowest respiration rate (mg g-1 h-1 of C-CO2) was in soils, followed by leaf litter and was higher in the treatments where soil and leaf litter were combined. The highest respiration rate was related to the combined treatments of soil and Bothriochloa pertusa litter. In conclusion, the rate of microbial respiration in soil is an important indicator of microbial activity and soil health. Measurement of microbial respiration rate can be used to assess soil health and monitor soil quality